Corifollitropin α followed by menotropin for poor ovarian responders' trial (COMPORT): a protocol of a multicentre randomised trial. Issue 6 (1st June 2013) - Polyzos, Nikolaos P; Camus, Michel; Llacer, Joaquin; Pantos, Konstantinos; Tournaye, Herman
Abstract : Background: Poor response to ovarian stimulation affects a significant proportion of infertile couples undergoing in vitro fertilisation (IVF) treatment. Recently, the European Society of Human Reproduction and Embryology developed new criteria to define poor ovarian response, the so-called Bologna criteria. Although preliminary studies in these patients demonstrated very low pregnancy rates, a recent pilot study has shown promising results in women <40 years old fulfilling the criteria, after treatment with corifollitropin α followed by highly purified menotropin (hpHMG) in a gonadotropin-releasing hormone (GnRH) antagonist setting. Corifollitropin α followed by menotropin for poor ovarian responders' trial (COMPORT) is a randomised trial aiming to investigate whether this novel protocol is superior to treatment with recombinant follicle-stimulating hormone (FSH) in an antagonist setting for young poor responders. Methods/design: COMPORT is a multicentre, open label, phase III randomised trial using a parallel two-arm design. 150 patients <40 years old fulfilling the 'Bologna criteria' will be randomised to corifollitropin α followed by hpHMG (group A) or recombinant FSH (group B) in a GnRH antagonist protocol for IVF/intracytoplasmic sperm injection (ICSI). The primary outcome is the ongoing pregnancy rate (defined as the presence of intrauterine gestational sac with an embryonic pole demonstrating cardiac activity at 9–10 weeks of gestation). Secondary outcomes are clinical and biochemical pregnancy rates and number of oocytes retrieved. Central randomisation will be performed using a computer-generated list and allocation concealment will be secured with the use of sealed-opaque envelopes. A sample size of 150 women is essential to detect a difference of 19.5% in ongoing pregnancy rates between group A (28%) and group B (8.5%) with a power of 85% and a level of significance at 0.05 using a two-sided Fisher's exact test.